AKTUALISASI MULTIPLE INTELLIGENCES PADA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN OUTBOUND DI TAMAN KANAK-KANAK ISLAM PELANGI ANAK NEGERI YOGYAKARTA - Lukman Lukman (PELANGI: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research is titled the actualization of multiple intelligences in children aged 5-6 years through outbound games in the Rainbow Islamic Kindergarten of Yogyakarta State Children. With the aim of analyzing and knowing the results of developing the multiple intelligences approach. This research is expected to contribute positively to the development of Early Childhood learning, especially in multiple intelligences learning in outbound games for Early Childhood, as well as reference material for Rainbow IslamicKindergarten, Yogyakarta Children and the wider community. This type of research is research (field research), namely researchers conduct direct research on the object under study and data collection found in the field. This research includes the type of qualitative research, namely research that intends to understand the phenomenon of what is experienced by the subject of research such as behavior, perceptions, motivations, actions, and others. Data collection techniques were carried out by observing passive participation, through observation, interviews and documentation, and triangulation. After the data is obtained, it checks the validity of the data, analyzes the data with steps of data reduction, data presentation, conclusions, and verification of data. Development of outbound learning is designed sothat children do not feel bored receiving learning in the classroom. The results of the research findings are: first, children can explore and express multiple intelligence in each playing activity using four types of steps,namely; (a) at the time of environmental arrangement, (b) on the footing before playing (circle time1), (c) during playing activities, (d) when stepping after playing (circle time 2 / recalling). Every outbound game always provides communication, counting, gesture, social, cooperation, naturalist, and moral values for children’s development. Second, supporting factors in the actualization of multiple intelligences in Early Childhood Through Outbound Games include; a conducive Taman Kanak environment, creative teachers, game tools that are already available, then supplemented with adequate facilities and infrastructure. While the inhibiting factors in the actualization of multiple intelligences in Early Childhood throughoutbound games include; the absence of good cooperation between teachers and parents of students, community environment, family environment, the presence of social media, and technological sophistication, so that children are very difficult to monitor.